Column Writing by Zafar Iqbal - Sadiq, Shakeel Amjad; Awan, Muhammad Asif (sourcecoder, 2024)
Zafar Iqbal was associated with Urdu literature since childhood. He started writing poetry during his college studies. His collection of poetry has been published in five volumes under the name "اب تک"which includes thirty of his ghazal collections. There are 3630 Ghazals and 32677 Poems in these collections. The happy thing is that despite his old age, his poetic and literary journey continues. A collection of his critical essays has been published in four volumes under the name of "لا تنقید" Fiqahya columns were printed under the title of "خشت زعفران" and then Faqahya columns were published under the title of "دال دلیا" in four volumes. The collections of Punjabi poetry have been published with the title "پنڈو کڑی" Zafar Iqbal holds a unique and high position in his Punjabi poetry, column, writing and criticism, but his distinction is his approach in Urdu ghazal writing. The description of diverse social, political and economic realities has earned him the sanctity of a multifaceted poet.